Neighbourhood social inclusion from the perspective of people with intellectual disabilities: Relevant themes identified with the use of photovoice. Issue 1 (5th July 2018) - Overmars‐Marx, Tessa; Thomése, Fleur; Meininger, Herman
Abstract: Background: Earlier studies show that to gain more understanding of the concept of social inclusion, the views and experiences of people with intellectual disabilities are needed. The aim of this study was to investigate their perspective on neighbourhood social inclusion from an ecological point of view. Method: We carried out a photovoice study with 18 people with intellectual disabilities in three neighbourhoods in the Netherlands. Participants took photographs in their neighbourhood they considered relevant, and these photographs were discussed during an interview. Results: Six themes emerged from qualitative analysis: attractiveness of the neighbourhood, social contacts in the neighbourhood, activities in the neighbourhood, social roles in the neighbourhood, independence and public familiarity. Conclusions: As regards neighbourhood social inclusion, participants were often focused on small and informal activities and situations. Public familiarity proved very important. Framing the concept of neighbourhood social inclusion within an ecological approach may help to better understand processes of social inclusion.